Comparison of the Analgesic Effect of Ketamine and Midazolam with Paracetamol (Acetaminophen) and Ketorolac in Renal Colic Patients: A Clinical Trail - Bahrami, Anvar; Jabbari, Latife; Zamanimehr, Nahid; AzizKhani, Leila (Galen Medical Journal, 2025)
Background: Renal colic is the most prevalent symptom of urinary stones, and it is quite painful. This study aimed to determine the effect of the Ketamine and Midazolam combination and compare it with the acetaminophen (paracetamol or Apotel) and Ketorolac (Toradol) combination in pain management of patients with renal colic in the emergency department (ED). Materials and Methods: In this double-blind clinical trial study, 200 renal colic patients admitted to the ED with more than 8 Numeric Rating Scale (NRS) of primary pain were divided into two groups by random blocking: one group received intravenous Ketamine (0.4 mg/kg), and intravenous Midazolam (at a dose of 0.016 mg/kg) and the other group received intravenous Ketorolac (30 mg) and intravenous acetaminophen (15 mg/kg). After that, we measured patients’ pain by NRS at 1, 5, 10, 15, 30, and 45 min after the procedure. The data were analyzed using IBM SPSS 21.0 software. Results: 124 (62.0%) of 200 patients were men. Initial pain scores were 9(10-9) for Ketamine + Midazolam and 10(10-9) for Acetaminophen + Ketorolac.Linear regression was performed to compare the two groups’ adjusted pain scores, correcting for initial pain. The ultimate pain score increased by.392 units for each unit of starting pain. Group and time had significant effects (5.553, -.035, P=.001, respectively). Acetaminophen + Ketorolac had a higher mean pain score than Ketamine + Midazolam at all post-intervention time intervals. During the trial, both groups’ discomfort decreased significantly. Conclusion: The combination of Ketamine and Midazolam was more effective than Acetaminophen and Ketorolac in relieving the pain in renal colic. Therefore, if routine medications are contraindicated, a combination of Ketamine and Midazolam is recommended for pain control in patients with renal colic.